Rhabdomyosarcoma as a very rare tumor in adult: Case series - Aslan, Ferit; Erdur, Erkan; Yıldız, Fatih (Journal of Surgery and Medicine, 2020)
Aim: Rhabdomyosarcoma is more frequent and has a better prognosis in children. In adults, it is relatively rare and has a worse prognosis. The most effective treatment is achieved with a multimodal approach. We aimed to share the clinical, pathological and survival results of 14 patients with adult rhabdomyosarcoma. Methods: In our study, we evaluated 14 patients with RMS who were followed up and treated between January 2000 and January 2018 in three medical oncology departments in Turkey. The uses of surgery, chemotherapy and radiotherapy for curative and palliative purposes were considered multimodal in all patients. Results: The median age of all patients was 44.5 years (range: 16-83). Ten (71.4%) of our patients were male. The tumors of nine (64.3%) of 14 patients were localized and 5 (35.7%) patients had metastatic disease. Five (55.6%) of 9 patients with localized disease developed relapse. Histological examination of the patients revealed that 10 (71.4%) had pleomorphic, 3 (21.4%) had alveolar and 1 (7.1%) had undifferentiated RMS. The median follow-up period of all patients was 14.6 (range; 2.3-267) months. Relapse-free survival (RFS) was 15.17 months (95% CI; 1.1-29.2). The time to progression of disease after metastatic first-line treatment (PFS) was 10.18 (95% CI; 7.08-13.2) months. At evaluation of the data, 9 patients had died. Median overall survival (OS) at local and metastatic stages were 29.3 months (95% CI; 20.8-37.9) and 11.2 months (95% CI; 9.29-13.1), respectively, while the OS of all participants was 22.8 months (95% CI; 0-47). Five-year OS was 28.2% (Standard error (SE); 13.4%) and 5-year relapse-free survival was 41.2% (SE; 17.3%). Conclusions: The multimodal approach is the best option in early and advanced stage rhabdomyosarcoma. Among our few patient series, clinic and survival results are consistent with the literature.